Effects of Long-Term Administration of Freeze-Dried Chokeberry Juice to Rats - Adamska, Teresa; Ewertowska, Małgorzata; Ignatowicz, Ewa; Kujawska, Małgorzata; Kidoń, Marcin; Arleta Matuszewska,; Oszmiański, Jan; Szaefer, Hanna; Jodynis-Liebert, Jadwiga (Journal of Pharmacy and Nutrition Sciences, 2014)
Polyphenolics can act as prooxidants leading to the generation of reactive oxygen species and electrophilic metabolites which bind to DNA, protein and glutathione. The aim of the present study was to evaluate potential adverse effects of the long-term dietary administration of freeze-dried chokeberry juice to rats. Groups of 8 males and 8 females were exposed via diet to 0; 2; 6; 10 g juice/kg feed for 90 days. Mean food consumption and mean body weight gain of treated animals were comparable with controls. Changes in some hematological parameters were sporadic and non-dose-responsive. Several statistically significant changes in clinical chemistry parameters were considered no toxicologically relevant since they were of small magnitude and lacked correlating findings in histopathology. Histopathological examination did not reveal any changes that could be attributed to chokeberry juice intake. Determination of oxidative damage markers in the liver demonstrated no damage of lipids, proteins and DNA. Chokeberry juice intake improved antioxidant status of rats as evidenced by a decrease in the level of lipid peroxidation, an increase in reduced glutathione concentration and an increase in some antioxidant enzymes activity. It could be concluded that freeze-dried chokeberry juice is safe at doses tested and can be used as a component of food supplements.